Man in uniform with "The Lyric" on his jacket. - (:unkn) unknown (Forsyth County Public Library, 2010)
Photo made in the 1900s. Alderman & Eutsler Studio opened in 1908.
Man in uniform with "The Lyric" on his jacket. This is possibly a man who worked in a theatre, called The Lyric. There was a Lyric Theatre in Winston-Salem in 1909, but changed its name to The Amuzu in 1910.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth